Photo-illuminated Glutathione Inactivates Alpha-2-macroglobulin: Spectroscopic and Thermodynamic Studies - Syed Saqib Ali; Haseeb Ahsan; Sana Ansari; Khan M Abdullah; Fahim Halim Khan (Cell and BioPharmaceutical Institute, 2022)
Background: Glutathione (GSH) is a principle thiol-containing tripeptide (cysteine, glutamic acid and glycine) antioxidant against free radicals and other harmful oxidants in cellular defence. The alpha-2-macroglobulin (α2M) is large tetrameric zinc-binding glycoprotein which inhibits proteinases regardless of their specificity and catalytic mechanism.Materials and Methods: The interaction of GSH was analyzed with α2M including the structural and functional alterations in α2M using various biochemical and biophysical methods. UV-visible and fluorescence spectroscopy were used to study the binding of α2M with GSH and Fourier transform infrared (FT-IR) spectroscopy was explored to study the structural change induced in α2M.Results: The results suggest that exposure of α2M to GSH decreases the antiproteolytic potential as suggested by the amidase assay. The UV-spectroscopic study showed the formation of α2M-GSH complex and fluorescence analysis showed significant quenching in fluorescence intensity of α2M suggesting GSH binding and structural alteration in the protein. FT-IR spectroscopy was explored to study the structural change induced in α2M which suggest that the secondary structure of α2M changes upon complex formation.Conclusion: Our studies show that interaction of α2M with photoilluminated GSH results in functional and conformational changes of the protein.Keywords: glutathione, GSH, alpha-2-macroglobulin, photo-illumination, ITC, FTIR